STUDENTS TRANSLATION OF ENGLISH TEXT INTO INDONESIAN TEXT AT THE FIFTH SEMESTER OF KHAIRUN UNIVERSITY - Mirna Bueke; Samsudin Hj Adam; Suratman Dahlan (Jurnal Bilingual, 2023)
This study aims to find out: (1) students' difficulties in translating English texts into Indonesian and (2) the causes of difficulties in translating texts at the fifth Semester students of English Language Education Study Program of Khairun University. This study applies a qualitative descriptive method and in analyzing data using content analysis. This study involved 12 participants. The research instrument used a test in the form of a literary text entitled "An Immortal Soul". The results showed that students had difficulty understanding the meaning of the text, because lack of vocabulary mastery, grammatical issues, and difficulty translating literary texts. The causes of these difficulties include a lack of background knowledge about literary texts, most of the students are still translating word for word and also cultural differences. This shows that fifth semester students still have difficulty translating English texts into Indonesian, especially in literary texts. As a result, students need more practice to get a good translation.